Nitrogen flows in global pork supply chains and potential improvement from feeding swill to pigs - Uwizeye, Aimable; Gerber, Pierre J.; Opio, Carolyn I.; Tempio, Giuseppe; Mottet, Anne; Makkar, Harinder P.S.; Falcucci, Alessandra; Steinfeld, Henning; de Boer, Imke J.M. (Resources, conservation and recycling, 2019)
•We modelled nitrogen flows, losses and efficiencies for global pork supply chains.•Significant variabilities exist for N use efficiency between regions and systems.•Main losses occur at feed production level, in the form of nitrates and organic N.•Swill feeding increases N use efficiency of pork supply chains, globally.•Enabling policies are needed to ensure quality and safety of using swill as feed. The global pork sector contributes to food security and supports livelihoods for millions of households but also causes nitrogen (N) pollution. Here we assess N flows, losses, and N use indicators for global pork supply chains, from “cradle-to-primary-processing-gate” and for three production systems: the backyard, intermediate and industrial systems. Subsequently, we evaluate the effects of feeding swill to industrial pigs on N flows and land use. To produce 3.5 Tg N of pork globally, 14.7 Tg N are lost into the environment, of which 68% is lost to watercourses in the form of nitrates and organic N and the reminder emitted to the atmosphere as N-gas (e.g., NH3, NOx and N2O). We found that the efficiency of N use, hotspot and magnitude of N losses per unit of area depend chiefly on the region (agro-ecological and economic context), origin of feed, and manure management systems. Swill feeding increases N use efficiency and reduces N losses at the feed production stage. It achieves a saving of 31 Mt of soybeans and 20 Mt of grains on dry matter basis, equivalent to 16 M ha of land used. Its adoption would require innovative policies to preserve food safety and public health. Future research may explore the feasibility and requirements to adopt swill feeding at a country level and may investigate potential impacts on other sustainability objectives.